2012
DOI: 10.1074/jbc.m112.355404
|View full text |Cite
|
Sign up to set email alerts
|

ATP Synthesis-coupled and -uncoupled Acetate Production from Acetyl-CoA by Mitochondrial Acetate:Succinate CoA-transferase and Acetyl-CoA Thioesterase in Trypanosoma

Abstract: Background: Mitochondrial acetate production is essential for viability of the procyclic trypanosomes and probably many other protists. Results:We identified an acetyl-CoA thioesterase (ACH) contributing to acetate production from acetyl-CoA. Conclusion: Acetate production by ASCT, but not by ACH, is involved in ATP production. Significance: In trypanosomes and probably other protists, ASCT/SCoAS cycle-derived ATP production can substitute for oxidative phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 40 publications
5
81
0
Order By: Relevance
“…1B). This is probably due to the limited capacity of acetate production, as previously proposed (50). The same analyses revealed that the ⌬ppdk/⌬pepck cell line behaves differently.…”
Section: Resultssupporting
confidence: 71%
“…1B). This is probably due to the limited capacity of acetate production, as previously proposed (50). The same analyses revealed that the ⌬ppdk/⌬pepck cell line behaves differently.…”
Section: Resultssupporting
confidence: 71%
“…This result is in agreement with previously published data indicating that no or very low amounts of acetate are produced from proline, whereas the degradation of threonine is the main source of acetate production under glucose-depleted conditions (9,46). Acetate can be produced in the mitochondrion from threoninederived acetyl-CoA via acetate:succinate CoA-transferase (ASCT)-dependent (47,48) and by acetyl-CoA thioesterase (ACH)-dependent pathways (49). An important difference between these pathways is that ASCT, forming the ASCT/ SCoAS cycle in association with succinyl-CoA synthase (SCoAS), results in the production of ATP via substrate level phosphorylation, whereas the ACH pathway does not lead to ATP production (47)(48)(49).…”
Section: Depletion Of Tbmcp5 and Its Effect On The Pcf Energymentioning
confidence: 99%
“…Acetate can be produced in the mitochondrion from threoninederived acetyl-CoA via acetate:succinate CoA-transferase (ASCT)-dependent (47,48) and by acetyl-CoA thioesterase (ACH)-dependent pathways (49). An important difference between these pathways is that ASCT, forming the ASCT/ SCoAS cycle in association with succinyl-CoA synthase (SCoAS), results in the production of ATP via substrate level phosphorylation, whereas the ACH pathway does not lead to ATP production (47)(48)(49). Silencing of SCoAS expression by RNAi confirmed that acetate could be exclusively produced from threonine by ACH (49).…”
Section: Depletion Of Tbmcp5 and Its Effect On The Pcf Energymentioning
confidence: 99%
See 1 more Smart Citation
“…These include: (a) the spontaneous hydrolysis of acetate phosphate to acetate and P i (Koshland, 1952;Di Sabato and Jencks, 1961); (b) aldehyde dehydrogenase activity that oxidizes acetaldehyde (from pyruvate decarboxylation) to acetate (Kirch et al, 2004(Kirch et al, , 2005Brocker et al, 2013); (c) acetyl-CoA hydrolase, which hydrolyzes acetyl-CoA to acetate and CoA without the production of ATP (Tielens et al, 2010); (d) acetate formation by AMP-forming acetyl-CoA synthetase (Takasaki et al, 2004;Yoshii et al, 2009); and (e) ASCT and SCL activities (van Grinsven et al, 2008;Millerioux et al, 2012). ASCT transfers the CoA moiety of acetyl-CoA to succinate and SCL converts succinyl-CoA back to succinate.…”
Section: Discussionmentioning
confidence: 99%